REVOLUTIONISING FINANCIAL DATA MANAGEMENT: THE CONVERGENCE OF CLOUD SECURITY AND STRATEGIC ACCOUNTING IN BUSINESS SUSTAINABILITY - Md Mahfuzur Rahman & Zihad Hasan Joy (International Journal of Management Information Systems and Data Science, 2024)
The acceleration of digital transformation in financial management necessitates an examination of the interplay between cloud security and strategic accounting, especially concerning business sustainability. This study conducts a qualitative analysis, employing semi-structured interviews and case studies, to explore the integration of cloud security measures with strategic accounting practices. The findings reveal a significant shift in organisational strategies, where cloud security is no longer seen merely as a defence mechanism but as a crucial enabler of sustainable business practices. Enhanced transparency and accountability stemming from secure cloud platforms are key to building stakeholder trust and meeting compliance. Despite persistent concerns over cyber threats, a growing trend towards adopting comprehensive cloud security strategies underpin strategic accounting efforts, highlighting a proactive stance in addressing potential risks. This study contributes to the literature by offering a nuanced understanding of how cloud security and strategic accounting coalesce to support sustainability, illustrating this integration's complexities and strategic imperatives.